Controlled-Release Iodine Fertilizer Improved Iodine Accumulation, Antioxidant Capacity, and Quality of Lettuce - Haining Chen; Faxiang Jiang; Huafei Zhou; Zhantian Zhang; Zhihan Zhang; Baoyou Liu (Agronomy)
To clarify the effects of newly developed controlled-release iodine fertilizer (CRIF) on enhancing lettuce (Lactuca sativa L.) iodine accumulation, improving the physiological traits, and reducing iodine leaching from soil, a greenhouse pot experiment was conducted. Polymer-coated iodate (PCIO), polymer-coated iodide (PCI), and two conventional iodine fertilizers—iodate (CIO) and iodide (CI)—were applied at a rate of 15 mg iodine per kg soil. The study found that the coating of iodine fertilizers had no significant effects on the biomass of lettuce. The iodine concentration in lettuce leaves subjected to PCIO treatment was elevated by 50.1% and 45.5%, respectively, in comparison to leaves treated with CIO and PCI. The soil-to-leaf transfer factor (TFleaf, dry weight basis) for plants treated with PCIO was significantly higher than that of PCI-treated plants. PCIO also significantly reduced iodine leaching by 46.3% compared to CIO. In lettuce leaves with PCIO treatment, the enzymatic activities of superoxide dismutase (SOD) and catalase (CAT) significantly increased by 50.8% and 27.6%, respectively. Likewise, malo-naldehyde (MDA) levels decreased by 23.2% compared to the control samples. PCIO also demonstrated advantages in enhancing the quality of the lettuce. In conclusion, the application of controlled-release iodine fertilizer could be a highly effective and eco-friendly approach to cultivating iodine-rich vegetables.